2003
DOI: 10.1038/sj.onc.1206732
|View full text |Cite
|
Sign up to set email alerts
|

Human DF3/MUC1 carcinoma-associated protein functions as an oncogene

Abstract: The human DF3/MUC1 mucin-like glycoprotein is aberrantly overexpressed by most carcinomas of the breast and other epithelia. The contribution of MUC1 overexpression to the malignant phenotype is, however, not known. In the present studies, we have stably expressed MUC1 in rat 3Y1 fibroblasts. MUC1-positive cells were selected from independent transfections. The results demonstrate that, as found in human carcinomas, MUC1 is expressed on the cell surface and as a complex with b-catenin in the nucleus of the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
169
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 185 publications
(175 citation statements)
references
References 18 publications
4
169
1
1
Order By: Relevance
“…Other studies have shown that phosphorylation of MUC1 by the epidermal growth factor receptor (25), c-Src (26), and protein kinase C␦ (PKC␦) (27) induces binding of MUC1 and ␤-catenin. These findings indicate that MUC1 functions by integrating signals from growth factor receptors, which also activate PI3K/Akt (1) and the Wnt pathway.Overexpression of MUC1 is sufficient to induce the transformation of rat 3Y1 fibroblasts (20). The present studies demonstrated that expression of MUC1 in 3Y1 cells is associated with the activation of the PI3K/Akt pathway.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…Other studies have shown that phosphorylation of MUC1 by the epidermal growth factor receptor (25), c-Src (26), and protein kinase C␦ (PKC␦) (27) induces binding of MUC1 and ␤-catenin. These findings indicate that MUC1 functions by integrating signals from growth factor receptors, which also activate PI3K/Akt (1) and the Wnt pathway.Overexpression of MUC1 is sufficient to induce the transformation of rat 3Y1 fibroblasts (20). The present studies demonstrated that expression of MUC1 in 3Y1 cells is associated with the activation of the PI3K/Akt pathway.…”
supporting
confidence: 62%
“…Overexpression of MUC1 is sufficient to induce the transformation of rat 3Y1 fibroblasts (20). The present studies demonstrated that expression of MUC1 in 3Y1 cells is associated with the activation of the PI3K/Akt pathway.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Estimates indicate that ~800,000 of the 1.4 million tumors diagnosed annually in the US overexpress MUC1. Recent studies have demonstrated that the overexpression of MUC1 induces transformation (6) and that the oncogenic sequences reside in the MUC1 C-terminal subunit (20,44). However, no information is available regarding the origin of the MUC1-C extracellular and cytoplasmic domains.…”
Section: Discussionmentioning
confidence: 99%
“…The MUC1 C-terminal subunit (MUC1-C) consists of a 58 amino acid extracellular domain, a 28 amino acid transmembrane domain and a 72 amino acid cytoplasmic tail (15). MUC1-C is targeted to the nucleus (6,10,(16)(17)(18) and mitochondria (8,19). In addition, MUC1-C stabilizes the Wnt effector, ß-catenin, through direct binding of the MUC1-C cytoplasmic domain (MUC1-CD) and the ß-catenin Arm repeats (20).…”
Section: Introductionmentioning
confidence: 99%